How the cladoceran heterogonic life cycle evolved—insights from gamogenetic reproduction and direct development in Cyclestherida. Issue 6 (21st October 2015) - Fritsch, Martin; Richter, Stefan
SUMMARY Here we document the early gamogenetic development of Cyclestherida, including a characterization of the nervous system. Resting eggs in Cyclestheria are protected by an ephippium, built by the major part of the carapace. The first stages of development are enclosed in an outer chorion and an inner vitelline membrane. After shedding of the chorion, the vitelline membrane inflates and later stages are free‐floating within the vitelline membrane. Only the juveniles are released from the vitelline membrane. Developmental stages of the gamogenetic direct development and of the parthenogenetic pseudo‐direct development are remarkably similar in Cyclestheria, both regarding external and nervous system development. Because of this high degree of correspondence, as well as the important differences to the anamorphic development in Spinicaudata, we suggest that the developmental stages from the gamogenetic life cycle evolved directly from the parthenogenetic life cycle. This implies that resting egg development in Cladoceromorpha does not correspond directly to the resting egg development in large branchiopods. This leads us to the conclusion that the entire heterogonous life cycle in Cladoceromorpha probably evolved anew.